Bioinspired Artificial Sensory Nerve Based on Nafion Memristor. (21st February 2019) - Zhang, Chen; Ye, Wen Bin; Zhou, Kui; Chen, Hong‐Ye; Yang, Jia‐Qin; Ding, Guanglong; Chen, Xiaoli; Zhou, Ye; Zhou, Li; Li, Fengjiao; Han, Su‐Ting
Abstract: Bioinspired artificial haptic neuron system has received much attention in the booming artificial intelligence industry for its broad range of high‐impact applications such as personal healthcare monitoring, electronic skins, and human–machine interfaces. An artificial haptic neuron system is designed by integrating a piezoresistive sensor and a Nafion‐based memristor for the first time in this paper. The piezoresistive sensor serves as a sensory receptor to transform mechanical stimuli into electric signals, and the Nafion‐based memristor serves as the synapse to further process the information. The pyramid‐structured sensor exhibits excellent sensitivity (6.7 × 10 7 kPa −1 in 1–5 kPa and 3.8 × 10 5 kPa −1 in 5–50 kPa) and durability (>7000 cycles), while the memristor realizes fundamental synaptic functions under low power consumption (10–200 pJ) and remains stable for over 10 4 consecutive tests. The integrated system can detect tactile stimuli encoded with temporal information, such as the count, frequency, duration and speed of the external force. As a proof‐of‐concept, English characters recognition with high accuracy can be achieved on the system under a supervised learning method. This work shows promising potential in bioinspired sensing systems owing to the high performance, excellent durability, and simple fabrication procedure. Abstract : An artificial haptic neuron system is designed by integrating a piezoresistive sensor and a Nafion‐based memristor for the first time. The pyramid‐structured sensor exhibits excellent sensitivity and durability, while the memristor realizes fundamental synaptic functions under low power consumption and remains stable for over 10 4 consecutive tests. The integrated system can detect tactile stimuli encoded with temporal information.